A Mobile-Based Digital Solution (Mozak) for Mosque Management in the Modern Era. - Adityo, R Dimas; Syafi'i, Syafi'i; Hidayat, M. Mahaputra; A.W, Satrio Cahyo; A, Sindi Hilda (STMIK Widya Cipta Dharma, 2025)
The mobile-based zakat management application serves as a modern solution to enhance the transparency and efficiency of zakat management at the local level. Mozak (Mobile Zakat) is an Android-based application implemented at Masjid Al-Ikhlas, Desa Janti, Sidoarjo, aimed at facilitating the collection, distribution, and monitoring of zakat. The application is designed with a user-friendly interface, allowing muzakki to pay zakat online and helping mosque administrators manage zakat data in real-time. This study evaluates the effectiveness of the Mozak application in supporting zakat activities at Masjid Al-Ikhlas, showing an improvement in operational efficiency. Additionally, the application enhances transparency in the distribution of zakat to mustahik